Association between firearms and mortality in Brazil, 1990 to 2017: a global burden of disease Brazil study - Deborah Carvalho Malta; Adauto Martins Soares Filho; Isabella Vitral Pinto; Maria Cecília de Souza Minayo; Cheila Marina Lima; Ísis Eloah Machado; Renato Azeredo Teixeira; Otaliba Libânio Morais Neto; Roberto Marini Ladeira; Edgar Merchan-Hamann; Maria de Fatima Marinho de Souza; Cíntia Honório Vasconcelos; et al. (BMC, 2020)
Abstract Background Brazil leads the world in number of firearm deaths and ranks sixth by country in rate of firearm deaths per 100,000 people. This study aims to analyze trends in and burden of mortality by firearms, according to age and sex, for Brazil, and the association between these deaths and indicators of possession and carrying of weapons using data from the global burden of diseases, injuries, and risk factors study (GBD) 2017. Methods We used GBD 2017 estimates of mortality due to physical violence and self-harm from firearms for Brazil to analyze the association between deaths by firearms and explanatory variables. Results Deaths from firearms increased in Brazil from 25,819 in 1990 to 48,493 in 2017. Firearm mortality rates were higher among men and in the 20-24 age group; the rate was 20 times higher than for women in the same age group. Homicide rates increased during the study period, while mortality rates for suicides and accidental deaths decreased. The group of Brazilian federation units with the highest firearm collection rate (median = 7.5) showed reductions in the rate of total violent deaths by firearms. In contrast, the group with the lowest firearm collection rate (median = 2.0) showed an increase in firearm deaths from 2000 to 2017. An increase in the rate of voluntary return of firearms was associated with a reduction in mortality rates of unintentional firearm deaths (r = −0.364, p < 0.001). An increase in socio-demographic index (SDI) was associated with a reduction in all firearm death rates (r = −0.266, p = 0.008). An increase in the composite index of firearms seized or collected was associated with a reduction in rates of deaths by firearm in the subgroup of females, children, and the elderly (r = −0.269, p = 0.005). Conclusions There was a change in the trend of firearms deaths after the beginning of the collection of weapons in 2004. Federation units that collected more guns have reduced rates of violent firearm deaths.